Inch‐sized 2D perovskite single‐crystal scintillators for high‐resolution neutron and X‐ray imaging - Boming Yang; Xiao Ouyang; Xue Zhao; Jie Su; Yang Li; Siyu Zhang; Xiaoping Ouyang (InfoMat)
Abstract Nuclear radiation detectors are critical to transient nuclear reaction imaging, medical diagnostic imaging, security checks, industry inspection, and so forth, with many potential uses limited by scintillator dimensions. Current scintillator crystals are limited by the long‐standing issues of hetero‐crystalline formation and consequently inferior crystal dimensions and quality. Particularly, the hybrid organic–inorganic perovskites (HOIPs) exhibit scintillation capability under X‐ray and fast neutrons within a single framework, owing to the presence of heavy elements and high hydrogen density groups, respectively. However, the achievement of high‐performance and large‐area imaging by HOIPs scintillators is impeded by the crystal growth technology. Herein, we propose an optimal crystal growth strategy and obtain an inch‐sized high‐quality (PEA)2PbBr4 single crystals (SCs) with a record dimension of 4.60 cm × 3.80 cm × 0.19 cm. Their application as synergistic scintillators in high‐energy rays and charged particles detection are investigated, which exhibit high light yield (38 600 photons MeV−1) and ultra‐fast decay times that are 4.89, 27.98, and 3.84 ns under the 375‐nm laser, γ‐ray, and α particles, respectively. Moreover, the (PEA)2PbBr4 SCs demonstrate a remarkably high spatial resolution of 23.2 lp mm−1 (at MTF = 20%) for X‐ray and 2.00 lp mm−1 for fast neutrons, surpassing the reported perovskites scintillators.